A two-stage system proposal based on a type-2 fuzzy logic system for ergonomic control of classrooms and offices. (April 2023) - Erozan, İhsan and Özel, Emre and Erozan, Damlanur
Abstract: For people who spend a long time indoors during the day, it is incredibly vital that their environmental conditions are ergonomically designed to provide comfort. However, keeping these comfort conditions at optimum limits during the day requires an important control activity. In this study, a two-stage system using type-2 fuzzy logic is proposed for the ergonomic control of indoor environments such as classrooms and offices. This system calculates the effective working time and time-dependent change in carbon dioxide levels in the first stage and evaluates the ergonomic comfort conditions in the second stage. To develop this system, temperature, humidity, and carbon dioxide levels were measured at different times of the day in university classrooms and the rooms of some faculty members. Based on the data obtained from these measurements, the proposed ergonomic control structure was modeled by using both type-1 and type-2 fuzzy logic systems. As a result, although it was seen that both fuzzy logic systems produced the same results in some examples, it was observed that the proposed type-2 fuzzy logic system produced better interpretations than type-1 in some of the others. Therefore, the type-2 fuzzy logic system is recommended for better ergonomic control in extremely fuzzy environments. Highlights: This study presents a fuzzy logic system for the ergonomic control of indoor environments such as classrooms and offices. The proposed system can determine "when or after how many minutes" the level will be adverse for people/workers. The proposed system can evaluate the suitability of the working environment in terms of ergonomics.